The Occurrence of Non-Alcoholic Fatty Liver Disease among Individuals with Diabetes Mellitus: A Comparative Study - Ashay Shah; Arifa Bakerywala; Riya N. Brahmbhatt; Heena Shaikh; Nidhi Shashikant Bhutak; Renu Singh (Journal of Pharmacy and Bioallied Sciences)
Aim: This research aimed to investigate the occurrence and trends of non-alcoholic fatty liver disease (NAFLD) in individuals diagnosed with type 2 diabetes mellitus. Material and Methods: During the course of the study, a total of 100 patients with a diagnosis of type 2 diabetes mellitus were enrolled by researchers, adhering to defined inclusion and exclusion criteria. The diagnosis of NAFLD was confirmed via ultrasonography, which revealed a bright liver appearance. Results: The ultrasonography analysis revealed that 50% of the patients were diagnosed with fatty liver, leading to their classification in group A. The remaining patients, who exhibited no signs of fatty liver, were assigned to Group B. Group A exhibited significantly higher levels of serum AST, serum ALT, and serum alkaline phosphatase in comparison to Group B. Group B showed an elevated Serum AST/ALT ratio when compared to group A. Conclusion: The rising rates of obesity are increasingly linked to a surge in conditions such as type 2 diabetes mellitus and non-alcoholic fatty liver disease, has rendered the management of these patients more complex than ever. Clinicians must recognize the extrahepatic manifestations associated with NAFLD, as early identification of T2DM is crucial for effectively managing these patients.